2017
DOI: 10.1039/c7sc02801f
|View full text |Cite
|
Sign up to set email alerts
|

Sensing iron availability via the fragile [4Fe–4S] cluster of the bacterial transcriptional repressor RirA

Abstract: The global iron regulator RirA controls transcription of iron metabolism genes via the binding of a fragile [4Fe–4S] cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 65 publications
9
61
1
Order By: Relevance
“…Nondenaturing ESI-MS, in which noncovalently bound cofactors are retained upon ionization, has been shown to be extremely useful for determining the nature of the cluster in [Fe-S] proteins ( 22 , 24 27 ). Application here gave a deconvoluted spectrum containing a small peak at 15,919 Da corresponding to the apoprotein with all four cysteines in disulfide bridges.…”
Section: Resultsmentioning
confidence: 99%
“…Nondenaturing ESI-MS, in which noncovalently bound cofactors are retained upon ionization, has been shown to be extremely useful for determining the nature of the cluster in [Fe-S] proteins ( 22 , 24 27 ). Application here gave a deconvoluted spectrum containing a small peak at 15,919 Da corresponding to the apoprotein with all four cysteines in disulfide bridges.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted protein, which is identical to one encoded by S. fredii NGR234, exhibits high sequence similarity to the RirA proteins of S. meliloti , A. tumefaciens and R. leguminosarum bv. viciae (93.5%, 83.4%, and 79.4% identity, respectively), and conserves the three Cys residues predicted to ligate iron–sulfur clusters in Rrf2 family regulators [20] (Figure S1). The genetic context of the rirA gene is similar in HH103 and in S. meliloti .…”
Section: Resultsmentioning
confidence: 99%
“…Under iron-replete conditions, this regulator acts as a repressor of many iron-responsive genes by binding to Iron-Responsive Operator sequences (5’-TGA-(N9)-TCA-3’) known as IRO boxes [14,19]. A recent study has demonstrated that R. leguminosarum RirA contains a [4Fe–4S] cluster and that the holoprotein ([4Fe–4S]RirA) binds to an IRO box sequence [20]. Interestingly, the [4Fe–4S] cluster is sensitive to iron levels but also to O 2 , with low iron concentrations and aerobic conditions promoting the conversion of [4Fe–4S] cluster to [2Fe–2S] and subsequent cluster loss, which relieves gene repression [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sinorhizobium meliloti , deletion of grx2 , coding for the sole class II Grx, leads to an impaired activity of the Fe–S containing aconitase and succinate dehydrogenase, to an increased intracellular iron content and to the deregulation of some genes controlled by the major transcriptional regulator of iron homeostasis RirA (rhizobial iron regulator) [ 40 ]. This suggests a direct role in the maturation of Fe–S proteins, but possibly other functions such as the regulation of the RirA regulator that senses the cellular iron and O 2 status through the conversion of a fragile [4Fe–4S] cluster into a [3Fe–4S] cluster [ 41–43 ]. One of the consequences of grx2 deletion was a defect in the development of symbiotic nodules with Medicago truncatula , thus impairing nitrogen fixation [ 40 ].…”
Section: Introductionmentioning
confidence: 99%